Pengembangan Keterampilan Public Speaking Dan Komunikasi Organisasi Pada Anggota Gerakan Mahasiswa Kristen Indonesia Cabang Denpasar - Cipta Dewi, Ni Nyoman; Mehang Tana, Markus (Dwijendra University, 2022)
Communication is a necessity for humans to interact with one another. Each individual has a specific purpose in establishing communication with others. By understanding and applying public speaking and organizational communication, organization members can find out how the development of public speaking and organizational communication for members of the Indonesian Christian student movement Denpasar branch. In a study entitled